Exploring molecular characteristics and interactions of blood stasis syndrome in ischemic heart failure by integrated multi-omics - Wang, Aolong; Wei, Jingjing; Qiao, Lijie; Li, Xingyuan; Li, Ming; Zhu, Xinfeng; Zhang, Yilin; Zhao, Qifei; Yu, Rui; Li, Bin; Wang, Xinlu; Zhu, Mingjun (Frontiers in Molecular Biosciences, 2025)
BackgroundIschemic heart failure (IHF) is one of the leading causes of death worldwide. In traditional Chinese medicine, blood stasis syndrome (BSS) is regarded as a core pathological feature of IHF. This study aims to clarify the main biological characteristics and underlying mechanisms of BSS in IHF.MethodsUsing an integrated multi-omics strategy combining transcriptomics, proteomics, and targeted metabolomics, we systematically analyzed the molecular characteristics of BSS in patients with IHF from multiple perspectives. By integrating multi-omics data and correlating them with clinical parameters, we identified a core molecular network associated with BSS. Key targets within this network were further validated using iPRM and RT-qPCR. ROC curve analysis and responses to pharmacological intervention were employed to confirm the diagnostic and therapeutic potential of these core molecular targets.ResultsA total of 435 differentially expressed genes, 176 differentially abundant proteins, and 40 differentially altered metabolites related to IHF with BSS were identified. Multi-omics analysis highlighted the involvement of the complement and coagulation cascade and B cell receptor signaling pathway. Moreover, targeted metabolomics suggested that metabolic pathways associated with BSS involve glycine, arginine, tryptophan metabolism, and fatty acid biosynthesis. Integrated multi-omics correlation analysis identified CD79A, CD79B, CD19, CD22, CR2, F2, F8, F9, C3, FN1, 5-hydroxyindolacetic acid, and 4-acetamidobutanoate as core molecular features, with significant correlations observed between these molecules and clinical indicators. iPRM and RT-qPCR validation confirmed that the expression trends of these core molecules are consistent with the sequencing results. Furthermore, cross-validation with Yiqi Huoxue formula intervention identified F2, F8, F9, and FN1 as four diagnostic and therapeutic targets for BSS.ConclusionThis multi-omics analysis reveals that immune dysregulation, inflammation, and impaired coagulation function are central to BSS in IHF. Key pathways involved include the complement and coagulation cascade as well as B-cell receptor signaling, with F2, F8, F9, and FN1 identified as potential diagnostic and therapeutic targets. These findings provide new molecular insights into BSS in IHF.